Stimulasi Kutaneus Slow Stroke Back Massage Terhadap Nyeri Dismenorea Primer Di Klaten - Wiwin Rohmawati; Lilik hartati (Universitas Muhammadiyah Klaten, 2019)
Menstruation is the process of releasing the uterine wall accompanied by bleeding and occurs repeatedly every month. There are still many adolescents who experience menstrual problems such as menstrual pain or dysmenorrhoea during menstruation. Primary dysmenorrhoea is menstrual pain without abnormalities in the reproductive organs caused by contractions of the uterine wall. There are two types of therapy to treat dysmenorrhoea, namely pharmacological and non-pharmacological therapy. Non-pharmacological therapy is wrong one is the cutaneous stimulation of the Slow Stroke Back Massage. This study aims to determine the effect of cutaneous stimulation Slow Stroke Back Massage on the level of primary dysmenorrhoea pain at the Putri Aisyiyah Tonggalan Klaten Orphanage.This type of research is pre-experimental with a one group pretest-posttest research design. The population in this study was 48 young women at the Putri Aisyiyah Tonggalan Klaten Orphanage in April 2017, with a sample of 33 adolescents using purposive sampling technique. Data analysis used the Wilcoxon signed rank test. The statistical test results with the Wilcoxon signed rank test (p <0.005) obtained the sig value. (2-tailed) of 0,000.The conclusions in this study indicate that there is an effect of cutaneous stimulation of Slow Stroke Back Massage on the level of primary dysmenorrhoea pain at the Putri Aisyiyah Orphanage at Tonggalan Klaten. Adolescents should always perform cutaneous stimulation of Slow Stroke Back Massage every menstrual cycle so that the pain level of primary dysmenorrhea can be reduced.